DEGUELIN, a novel anti-cancer agent, inhibits tumor aggressiveness and increases docetaxel efficacy in lung cancer cells - Cengiz, H.; Kocdor, M. A.; Aydin, S.; Kocdor, H. (Wiley, 2017)
[Abstract Not Available]
42nd Congress of the Federation-of-European-Biochemical-Societies (FEBS) on From Molecules to Cells and Back -- SEP 10-14, 2017 -- Jerusalem, ISRAEL